Identifying prominent actors in historical networks: The case of the New Education movement - Luoto, Lauri (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Social network analysis is becoming increasingly popular for studying the past. However, during the last decades, studies have applied pre-collected datasets for social network analysis, which limits the use of the method to cases where such data is available. This article presents another approach whereby two-mode network data are collected from less structured documentary sources, and the findings are enriched with documentary evidence. The approach is used to analyze how 42 notable members of the British New Education movement between 1905 and 1935 were affiliated with 31 organizations. The analysis provides empirical support for the previously proposed idea that there were two kinds of prominence within the movement: that of conveners, who formed close-knit groups with like-minded people, and that of mediators, who built bridges between such groups. Moreover, we discuss how this structure helped the movement to achieve its goals of more up-to-date, equally available education. The method presented in the article is suitable for researchers working with bibliographical or archive material in various domains.